Improving outpatient warfarin use for hospitalized patients with atrial fibrillation - Touchette DR; McGuinness ME; Stoner S; Shute D; Edwards JM; Ketchum K (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Atrial fibrillation affects an estimated 5 million Americans and accounts for approximately 15% of all strokes. Few studies have successfully addressed patient screening, assessment, and introduction of appropriate antithrombotic therapy in patients with atrial fibrillation. Objective: To assess whether an intervention improved planned antithrombotic prescribing at the time of discharge in hospitalized patients. Methods: The study was a prospectively designed, retrospectively evaluated, non-blinded, historical control study of a pharmacist-initiated intervention. The intervention, consisting of pharmacist review and assessment of antithrombotic prescribing in patients with non-valvular atrial fibrillation, was conducted in an urban teaching hospital. Results: Although antithrombotic prescribing was not significantly higher at discharge in the 252 enrolled subjects (control 67.3% vs. intervention 70.8%; p = 0.58), a significantly greater number of patients had a written discharge plan for antithrombotic therapy (control 73.5% vs. intervention 88.3%; p < 0.01). The adjusted odds ratio that the study group was associated with an improvement in planned or actual warfarin use was 2.46 (95% CI 1.63-3.74). In addition, clinicians adhered to guidelines for antithrombotic therapy in patients with atrial fibrillation more frequently in the intervention group (control 70.4% vs. intervention 88.2%; p < 0.01). Conclusion: A program designed to identify hospitalized patients with non-valvular atrial fibrillation, assess their need for stroke prophylaxis, and initiate appropriate antithrombotic therapy led to an increase in planned antithrombotic, and most importantly, warfarin use upon discharge from the hospital. Confirmation that an increase in planned antithrombotic use upon discharge results in an actual increase in use after discharge is needed to determine the true effectiveness of this intervention.